Photoconductivity of solution-processed MoS2 films - Mc Closkey, David; Donegan, John; Coleman, Jonathan (My University, 2013)
Solution-exfoliated MoS2 nano-platelets were formed into thin films by deposition onto a water surface followed by transfer to indium tin oxide coated glass. After drying, a gold electrode was evaporated on top to give a sandwich structure with quasi-Ohmic contacts. Illumination of this device with broadband light of ~1 kW/m2 intensity gave a fourfold increase in conductivity. The photocurrent increased sub-linearly with intensity and exponentially with time indicating the presence of traps. The photo-responsively was ~10-4 A/W at 15 V, competitive with other 2-dimensional photoconductors. This work demonstrates the potential for liquid-exfoliated, inorganic nanosheets to be fabricated into low-cost optoelectronic devices.
PUBLISHED
Cited by 1
Keywords: MoS2 nano-platelets